-6x+12=2(6-8x)

Simple and best practice solution for -6x+12=2(6-8x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6x+12=2(6-8x) equation:



-6x+12=2(6-8x)
We move all terms to the left:
-6x+12-(2(6-8x))=0
We add all the numbers together, and all the variables
-6x-(2(-8x+6))+12=0
We calculate terms in parentheses: -(2(-8x+6)), so:
2(-8x+6)
We multiply parentheses
-16x+12
Back to the equation:
-(-16x+12)
We get rid of parentheses
-6x+16x-12+12=0
We add all the numbers together, and all the variables
10x=0
x=0/10
x=0

See similar equations:

| √x+5=3 | | 2x+0,4x=2943 | | 7/3+3m/7=64/21 | | k/2+1-1K=2k | | 11x-12+3x+18=x | | 3k+17-9k=20 | | m÷10=16 | | 7x-2(x-3)=5(x+1)+4 | | 7(x-7)+3=7(x+5) | | 3a^2+2a+1=0 | | 12a-7=4a+9 | | 4-6a+4a=-1-5(7-2a | | r+3=-6,1/2 | | |9m|=81 | | 6(x+2)+6=6x+6 | | 5x-27/3=4 | | 3n-3=4n+1= | | 200=x-9 | | 5x^2-5x+26=0 | | 5n=n+108 | | 6=10x-4x | | 11x-12+3x+18=0 | | 2(x+7)+3x-6=182 | | -3w+7=-4 | | 5x+3=-1+3x | | 4x-(7+2x)=21 | | 3=2|1/4s-5|+3 | | -6x+12=2(6-8×) | | -6(8+6a)-8=30+7a | | z/5=9 | | 5x+3=-1=3x | | (x^2+1)(2x+1)-5(2x+1)=0 |

Equations solver categories